An interventive study of the effects of therapeutic lifestyle changes and simvastatin on the insulin sensitivity status of non obese hyperlipidaemic subjects - Nor Azwany, Yaacob
Obesity, hyperlipidaemia and insulin resistance are known to have relationship thus making it important to look into the insulin resistance in a group of non-obese hyperlipidaemic subjects. This study was designed to determine insulin sensitivity and secretory status of non-obese normoglycaemic subjects, and to find out the relationship between hyperlipidaemia and insulin sensitivity in a non-obese population. In addition, the second phase of this study looked at the effects of lipid lowering interventions on insulin sensitivity in h)'perlipidaemic subjects. A cross sectional study involving 246 nonobese (BMI<25 kg/m2 ), waist circumference male<l 02cm, female <88cm) and nondiabetic subjects aged between 30-60 years was carried out. The subjects underwent OGTT, LFT and RFT to exclude type 2 diabetes, IGT, IFG, renal and liver diseases. Fasting plasma glucose, fasting insulin and lipid profile were measured. Insulin sensitivity and secretory status were computed using the homeostasis model assessment (HOMA) software to obtain HOMA%S, HOMA%B and HOMA-IR. The subjects were divided into two groups according to their lipid status and their insulin sensitivity was compared between the two groups. Two groups of 28 non-obese hyperlipidaemic and 28 normolipidaernic subjects participated in the intervention study. They underwent 3 months of therapeutic lifestyle changes (TLC) regimen after which they were again divided into TLC and Simvastatin groups and for the subsequent three months went through either TLC only or TLC plus Simvastatin. Finally their insulin sensitivity and lipid status were assessed again. The hyperlipidaemic subjects showed substantially lower insulin sensitivity and higher insulin resistance in comparison to normolipidaemic subjects. The adjusted mean of HOMA%S of hyperlipidaernic and normolipidaemic subjects were 80 and 155 (p<O.OOOl) respectively. Insulin secretory status as expressed by the mean of HOMA%B was 178 and 116 for hyperlipidaernic and normolipidaemic subjects respectively. It indicates that the B cells of hyperlipidaemic subjects have to secrete more insulin to overcome the lowered insulin sensitivity. Intervention by both TLC and Sirnvastatin showed significant reduction of insulin resistance (62.3% improvement of HOMA-IR in TLC group and 51.44% in Sirnvastatin and TLC group) and improvement of insulin sensitivity (142% improvement of HOMA%S in TLC group and 122% in Sirnvastatin and TLC group) in hyperlipidaernic subjects with reduction of lipid levels. It can thus be concluded that, insulin sensitivity of otherwise healthy nonobese hyperlipidaemic subjects is lower than norrnolipidaemic subjects. Therapeutic life style changes is able to improve the insulin sensitivity in this group of subjects .